2004
DOI: 10.1212/01.wnl.0000145708.03876.c3
|View full text |Cite
|
Sign up to set email alerts
|

Statin-associated exacerbation of myasthenia gravis

Abstract: Myasthenia gravis (MG) can be exacerbated by a variety of medications, which increase weakness by interrupting neuromuscular junction transmission. Statins, which lower lipids by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, are not commonly known to worsen MG or have activity against the neuromuscular junction. 1 One report suggested that statin therapy produced ocular myasthenia. 2 However, based on the case description, it is not clear that this patient had MG. 3 We present a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…In severe case, respiratory difficulty can be seen and this can be a fatal condition in acute medicine. Several drugs are listed and reported as cause of exacerbation of MG. Those common drugs are antilipemic drug, steroid and antibiotic [5,6]. Antibiotic is a group of common drugs used at present.…”
Section: Discussionmentioning
confidence: 99%
“…In severe case, respiratory difficulty can be seen and this can be a fatal condition in acute medicine. Several drugs are listed and reported as cause of exacerbation of MG. Those common drugs are antilipemic drug, steroid and antibiotic [5,6]. Antibiotic is a group of common drugs used at present.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Cartwright et al 2 reported a patient with MG associated with statin use. Their patient, a 55-year-old man without prior history of myasthenia, developed recurrent dysarthria upon statin use.…”
Section: Background On Statins and Myasthenia Gravismentioning
confidence: 99%
“…Although statins are believed not to interfere with neuromuscular junction physiology, possible mitochondrial dysfunction on the mitochondria-rich preand postsynaptic interfaces of the motor end-plate could impair transmission in the neuromuscular junction and thus worsen myasthenic weakness. 2 It is also possible that some MG patients develop a statin-induced myopathy that leads to exacerbation of weakness. A relationship between statin-induced myopathy and immune-mediated disease was recently suggested in an abstract presented at the 2008 meeting of the American Academy of Neurology (Katzberg H, Miller RG, Grable P, Srinivasan J, Greenberg SA, Katz J, Amato A: "A necrotizing myopathy associated with statin use is responsive to immunomodulatory agents," Poster P02.131, 60th Annual Meeeting of the American Academy of Neurology, April 2008).…”
Section: Statins: Mechanism Of Action In Patients With Mgmentioning
confidence: 99%
“…Im ei ge nen Pa ti en ten gut konn te nur in ei nem sehr ge rin gen Teil die ser Pa ti en ten eine addi ti ve neu ro mus ku lä re Er kran kung nachge wie sen wer den, die aber im mer dif feren zi al di ag nos tisch ab zu klä ren ist. In Einzel fäl len wur den un ter Sta ti nen auch Derma to myo si tis und Po ly myo si tis ähn li che Symp to me, die Ex azer ba ti on ei ner Myasthe nia gra vis und pe ri phe re Neu ro pa thien be schrie ben [14,15,16,17,18,19,20].…”
Section: Kli Ni Sche For Menunclassified